An investigation into staff burnout in forensic hospitals - Shaw, Emily (2019)
This thesis provides a broad investigation into the issue of burnout in forensic hospital workers. The methods used include a critical review of a psychometric measure, a systematic review, a quantitative research study and a qualitative research study. To begin with, a critique of the Maslach Burnout Inventory (Maslach & Jackson, 1981; Maslach et al., 1996) assessed the psychometric properties of the tool, its applicability within occupational settings and its research use. The MBI is an assessment measure, used in many of the studies included in the systematic review and also in the quantitative research study. A number of limitations of the MBI were highlighted, including its self-report nature and the ongoing controversy regarding the number of dimensions that the MBI encompasses. However, the MBI has regularly demonstrated excellent levels of reliability and validity across a range of samples, cultures and professions. Therefore, it is concluded that the MBI is an effective tool for measuring burnout across a range of occupational settings. A systematic review of the existing literature identified a number of different risk factors for burnout in forensic hospital workers. Many variances were observed across studies, however, some commonalities were detected and the risk factors identified were grouped into four separate sub-categories: organisational/occupational factors, clinical factors, personal and individual factors and feeling detached from the outside world. The quantitative research study investigated the level of burnout experienced in a sample of 173 forensic hospital workers and the risk factors which may predict the development of burnout. When the results were compared to the normative data, it became apparent that participants were reporting higher than average levels of burnout. Moreover, quantitative outcome measures also yielded some statistically significant results regarding the associated risk factors for burnout, which included gender, age, length of time at the organisation, job role, children and level of education. Ward level of security and client group were also considered in relation to staff burnout. The clinical implications and the research implications of the findings are both discussed, with the findings of the study providing ideas and directions for future research. The qualitative research study explored the experiences of 12 forensic hospital workers using thematic analysis. The data analysis yielded ten sub-themes, grouped under five superordinate themes, which were all perceived to contribute to feelings of stress and burnout at work. The themes identified through the data analysis included: inadequate resources (difficulty accessing support and training needs), the daily chaos (the nature of working with forensic patients and running the ward), no sense of community (problematic relationships with colleagues and a fractured team), consequences of the job (impact on my personal life and impact on my health) and rewarding our efforts (limited recognition and why I still do it). The findings are discussed in terms of practical implications for the organisation and a number of interventions to reduce burnout in forensic hospital staff are also suggested.